Post-fire assessment of mechanical properties of concrete with the use of the impact-echo method. (15th October 2015) - Krzemień, Katarzyna; Hager, Izabela
Highlights: The impact-echo device was used to test concrete damage due to high temperature exposure. The resonance frequency of obtained signal decreases with higher thermal damage. The propagation velocity slows with higher level of thermal damage of concrete. The formulas for concrete mechanical properties evaluation by impact-echo method were established. Abstract: The paper presents the nature of elastic wave transition obtained in the time domain and the wave propagation velocity for the impact-echo method employed on the surface of concrete cubes 0.15 × 0.15 × 0.15 m 3 subjected to heating in the temperature range of 200–1000 °C. The relations between the characteristics of the obtained impact-echo signal and the mechanical properties of concrete subjected to high temperature were presented as regression curves. The paper proposes certain formulas to be employed while assessing fire-damaged concrete element. The results obtained on fire damaged concrete slab 1.2 × 1.0 × 0.3 m 3 indicate a strong relation between the impact-echo parameters and the mechanical properties of concrete.